Companion to sexuality studies - Naples, Nancy A. (Wiley Blackwell, 2020)
An inclusive and accessible resource on the interdisciplinary study of gender and sexuality Companion to Sexuality Studies explores the significant theories, concepts, themes, events, and debates of the interdisciplinary study of sexuality in a broad range of cultural, social, and political contexts. Bringing together essays by an international team of experts from diverse academic backgrounds, this comprehensive volume provides original insights and fresh perspectives on the history and institutional regulatory processes that socially construct sex and sexuality and examines the movements for social justice that advance sexual citizenship and reproductive rights. Detailed yet accessible chapters explore the intersection of sexuality studies and fields such as science, health, psychology, economics, environmental studies, and social movements over different periods of time and in different social and national contexts. Divided into five parts, the Companion first discusses the theoretical and methodological diversity of sexuality studies.Subsequent chapters address the fields of health, science and psychology, religion, education and the economy. They also include attention to sexuality as constructed in popular culture, as well as global activism, sexual citizenship, policy, and law. An essential overview and an important addition to scholarship in the field, this book: Draws on international, postcolonial, intersectional, and interdisciplinary insights from scholars working on sexuality studies around the world Provides a comprehensive overview of the field of sexuality studies Offers a diverse range of topics, themes, and perspectives from leading authorities Focuses on the study of sexuality from the late nineteenth century to the present Includes an overview of the history and academic institutionalization of sexuality studies The Companion to Sexuality Studies is an indispensable resource for scholars, researchers, instructors, and students in gender, sexuality, and feminist studies, interdisciplinary programs in cultural studies, international studies, and human rights, as well as disciplines such as anthropology, psychology, history, education, human geography, political science, and sociology.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; premier cycle; psychologie; queer; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; thématiques; études de genres; études des sexualités

Queering borders: Language, sexuality and migration - Murray, David A.B. (Journal of Language and Sexuality, 2014)
Preface to the special issue on queering borders in the journal of language and sexuality.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; canada; cours; discipline; histoire et politique; identités LGBTQIA2+; migration; migrations queer; premier cycle; queer; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

Le prix à payer pour devenir sujet de droit: la sélection des réfugiés allosexuels au Canada - Ricard, Nathalie (Alterstice, 2011)
Depuis les années 1990, le Canada accepte des réfugiés persécutés en raison de leur orientation sexuelle. Le statut de réfugié est octroyé par les membres de la Commission de l’immigration et du statut de réfugié qui évaluent la preuve de l’orientation sexuelle et de la persécution des personnes demandant asile. Or comment prouve‐t‐on sa sexualité et sa victimisation lorsque l’on a cultivé le silence au sujet de son identité, par peur des représailles, et que le pays d’où l’on vient ne produit pas de documents au sujet de la violence homophobe ? Jusqu’à présent, l’anthropologie ne s’était pas intéressée à la question des réfugiés issus des minorités sexuelles. De leur côté, plusieurs juristes ont cherché à savoir si l’accès à l’asile était équitable pour ces personnes. Les chercheurs se sont peu attardés, toutefois, au langage du droit que ces personnes sont obligées d’utiliser pour se faire reconnaître. Cet article explore les enjeux soulevés par le témoignage des demandeurs et demandeuses d’asile issus des minorités sexuelles, en portant une attention particulière aux exigences du discours juridique qui tend à réifier les dimensions culturelles et sexuelles de la subjectivité. Ainsi, les difficultés de dire la violence ne relèveraient pas uniquement des effets traumatiques de cette dernière, mais aussi du régime d’intelligibilité de la personne qui reçoit le témoignage. Les fonctionnaires canadiens gagneraient à être sensibilisés aux différences culturelles et aux rouages de l’homophobie, à ceux de leur pays comme à ceux dans d’autres sociétés, afin que le processus asilaire soit plus équitable.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; anthropologie; approches et analyses; canada; cours; discipline; droits; identités LGBTQIA2+; justice sociale; migration; minorités sexuelles; premier cycle; périodes historiques; queer; ressource en ligne; réfugiés; régions géographiques; sciences humaines; sex2283; thématiques

L'anthropologue et le système sexe/genre - Handman, Marie-Élisabeth (Connexions, 2008)
Cet article s’appuie sur le texte de N.-C. Mathieu concernant les rapports entre le sexe et le genre que l’on trouve dans les différentes sociétés. Elle dénombre trois modes de catégorisation de ces rapports : I. le sexe impose le genre, II. le genre prime le sexe, III. le sexe n’est pas pertinent, seul compte le genre qui, socialement construit, peut être déconstruit, donnant aux individus la possibilité d’en changer quand ils le souhaitent. La connaissance des modes d’insertion dans les sociétés exotiques de personnages considérés en Occident comme déviants, notamment ceux qui relèvent d’un « troisième sexe soxial », permet d’accepter certains aspects de la pensée queer, sans en adopter le style souvent agressif envers les hétérosexuels et sans « jeter le bébé avec l’eau du bain ».
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; genre; identités LGBTQIA2+; premier cycle; queer; ressource en ligne; sciences humaines; sex2283; sexe; thématiques

Make Room for Daddy: Anxious Masculinity and Emergent Homophobias in Neopatriarchal Politics - Stein, Arlene (Gender and Society, 2005)
What are the sources of continuing antipathy toward homosexuality, and what might they tell us about changing forms of American masculinity? This article documents some emergent homophobias circulating among conservative activists in relation to campaigns against gay rights in the early 1990s and against gay marriage in 2004. As feminist critiques of traditional masculinity make their way into conservative rhetoric and as men struggle to define a role that maintains male authority without sounding overly authoritarian, new forms of homophobia have emerged that are compatible with conservatives' quest to be seen as compassionate protectors of the family.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; homophobie; hétérosexisme; masculinité; militance; patriarcat; premier cycle; périodes; périodes historiques; régions géographiques; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; états-unis

The trouble with nature: sex in science and popular culture - Lancaster, Roger N. (University of California Press, 2003)
Roger N. Lancaster provides the definitive rebuttal of evolutionary just-so stories about men, women, and the nature of desire in this spirited expose of the heterosexual fables that pervade popular culture, from prime-time sitcoms to scientific theories about the so-called gay gene.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme pop; genre; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; soc2014; thématiques; études culturelles

Marché au sexe - Rubin, Gayle; Butler, Judith P.; Sokol, Eliane (EPEL, 2001)
"Aucun amateur de cuisine épicée ne se verra privé de liberté ou victime d'ostracisme pour avoir satisfait ses papilles gustatives. En revanche, on peut être jeté en prison pour trop aimer les chaussures en cuir. De même, l'homosexualité, le sida, la pornographie, le transsexualisme, et aujourd'hui la pédophilie, donnent-ils lieu à ce que Gayle Rubin appelle une " panique sexuelle ". Chaque panique désigne une minorité sexuelle, généralement inoffensive, comme population-cible. Au terme du processus, celle-ci se trouve décimée, et la société tout entière, juridiquement et socialement, réorganisée. Gayle Rubin a jeté les bases d'un champ autonome d'études sur le sexe où désir, jouissance et diversité érotique, pourraient trouver leur raison théorique et politique. Les trois textes publiés ici s'inscrivent dans une filiation politique (le féminisme, la nouvelle gauche, les luttes antiracistes, les luttes pour les droits civiques) et théorique (les sexologues, Freud, Lacan, Marx, Foucault, Derrida). Les paradigmes ne valent rien sans l'enquête de terrain, et rien non plus s'ils ne s'actualisent en choix de stratégie et de tactique politiques. L'ensemble s'éclaire du partiel, le partiel de l'ensemble. Nous sommes loin ici du communautarisme béat qu'on prête parfois en France aux intellectuels américains. Qu'on lise les critiques acerbes de Judith Butler sur les replis identitaires : les lesbiennes n'ont rien d'autre en commun que leur expérience du sexisme et de l'homophobie. Ou ses réserves sur le coming out : " La sexualité reste-t-elle sexualité quand elle est soumise à un critère de transparence et de révélation? Une quelconque sexualité serait-elle possible sans cette opacité qui a pour nom inconscient? " Gayle Rubin et Judith Butler soulignent constamment la nécessité de ne pas troquer une violence contre une autre, une démonologie religieuse contre une démonologie laïque, laissant ainsi sa chance à l'érotologie moderne. (Éditeur).
Contenue: Entretien : Marché au sexe / Gayle S. Rubin et Judith Butler – Penser le sexe / Gayle S. Rubin – Imitation et insubordination du genre / Judith Butler.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; hétérosexisme; identités LGBTQIA2+; lesbianisme; lit3220; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex3383; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; théories féministes; transféminisme; états-unis

Looking queer: body image and identity in lesbian, bisexual, gay, and transgender communities - Atkins, Dawn (Haworth Press, 1998)
Looking Queer: Body Image in Lesbian, Bisexual, Gay, and Transgender Communities contains research, firsthand accounts, poetry, theory, and journalistic essays that address and outline the special needs of sexual minorities when dealing with eating disorders and appearance obsession. Looking Queer will give members of these communities hope, insight, and information into body image issues, helping you to accept and to love your body. In addition, scholars, health care professionals, and body image activists will not only learn about queer experiences and identity and how they affect individuals, but will also understand how some of the issues involved affect society as a whole. Dismantling the myth that body image issues affect only heterosexual women, Looking Queer explores body issues based on gender, race, class, age, and disability. Furthermore, this groundbreaking book attests to the struggles, pain, and triumph of queer people in an open and comprehensive manner. More than 60 contributors provide their knowledge and personal experiences in dealing with body image issues exclusive to the gay and transgender communities, including: exploring and breaking down the categories of gender and sexuality that are found in many body image issues finding ways to heal yourself and your community discovering what it means to “look like a dyke” or to “look gay” fearing fat as a sign of femininity determining what race has to do with the gay ideal discussing the stereotyped ”double negative”–being a fat lesbian learning strategies of resistance to societal ideals critiquing ”the culture of desire” within gay men’s communities that emphasizes looks above everything else Revealing new and complex dimensions to body image issues, Looking Queer not only discusses the struggles and hardships of gay, lesbian, bisexual, and transgendered persons, but looks at the processes that can lead to acceptance of oneself. Written by both men and women, the topics and research in Looking Queer offer insight into the lives of people you can relate to, enabling you to learn from their experiences so you, too, can find joy and happiness in accepting your body.
Section: li, 467 p
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; image corporelle; intersectionnalité; premier cycle; queer; régions géographiques; sciences humaines; soc2014; thématiques; troubles alimentaires; états-unis

Le sexe biologique et sa relation au sexe social - Peyre, Evelyne; Wiels, Joëlle (Les Temps modernes, 1997)
http://transidentite.free.fr/oms/peyre_wiels-les_temps_modernes1997.pdf
Keywords: anthropologie; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; genre; identités LGBTQIA2+; lit2815; lit3220; lit3495; premier cycle; ressource en ligne; sciences humaines; sexe biologique; thématiques

Les transgressions du sexe et du genre à la lumière des données ethnographiques - Mathieu, Nicole-Claude (Sexe et genre : de la hiérarchie entre les sexes, 1991)
Keywords: 1900-1999; 1980-1989; anthropologie; approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sexe/genre; thématiques